The Past, Present, and Future: A Discussion of Cadaver Use in Medical and Veterinary Education - Varner, Caitlin; Dixon, Lucinda; Simons, Micha C. (Frontiers in Veterinary Science, 2021)
Cadaver usage in medical training, although controversial, has persisted over centuries. In veterinary education various methods have been proposed to either improve cadaver preservation, reduce cadaver use, or to replace cadavers entirely, but to date few have gained popularity. This manuscript seeks to: (i) describe the history of cadavers in medical and veterinary education; (ii) compare available cadaveric preservation methods; (iii) reflect on applications of cadaver use in the educational setting; (iv) discuss alternatives to traditional cadaver use; and (v) consider the perceptions of the stakeholders who use them.